(untitled) (Semiárida, 2020)
The aim of this work was to identify native and naturalized forage species from the islands of the delta of the Paraná River and to study the fractions that are degraded in rumen. Samples of Eichhornia crassipes (Camalote, CA) and Panicum elephantipes (Canutillo, CN) were taken from the Parana islands. Their chemical composition was determined: Dry Matter (DM %), Ethereal Extract (EE), Ashes (A), Crude Fiber (CF), and Crude Protein (CP; N x 6,25) and the rumen degradation kinetics was determined in sacco for (DR) DM and CP. Data were analyzed with ANOVA Scheffe’s test (P > 0.05) and DR adjusted to the following model: DR%= a + b (1 - e-ct), where is a: soluble fraction, b: slow degradable fraction, c: degradation rate, and a+b: potentially degradable fraction. CA showed 58 % less DM, similar EE and 35.5; 14.1 and 30.9 % more A, CF, and CP respectively, than CN. Degradable fractions in rumen were: DM fraction a: 18 and 21.6 and CP: 17.5 and –4 %, DM fraction b: 50.9 and 41.5 and CP: 42.6 and 80.4 %, degradation DM rate: 0.019 and 0.0384 and CP: 0.033 and 0.048 %/h and a+b fraction of DM: 69 and 63.1 and CP: 60.0 and 76.4 in CA and CN, respectively. CA showed a higher solubility and lower fractions of b, c and a + b of protein than CN. Though CN and CA, appear to be an interesting dietary source for ruminants, showed a lower degradability than known cultivated forage species.